Penggunaan Lks Elektronik Bermuatan Multimedia Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Sekolah Dasar - Ermelinda Yosefa Awe; Maria Patrisia Wau (Peneliti.net, 2022)
This study aimed at determining thematic learning activities and achievement using electronic student worksheets containing multimedia on the theme of the area where I live. This type of research was Classroom Action using Kemis and Mc Taggart which consists of planning, implementation and observation, and reflection. The subject of this study was the fourthgrade students of Zaa State Primary School totaling 25 students. While the object in this study was thematic learning activities and outcomes of fourth grade students at Zaa State Primary School using electronic student worksheets. Methods of data collection were using the method of observation and tests. The instruments used were observation sheets and multiple-choice tests which were conducted at the end of each cycle. Data were analyzed using quantitative descriptive analysis. The result of data analysis showed that the learning activity variable in the first cycle the average value was 62.36 with percentage of 62.36% being in quite active category and for the learning outcome variable, the average value was 62.42 with percentage of 62.42. % being in good enough category. In the second cycle of thematic learning activities the average value was 83.8 with a percentage of 83.8% being in the very active category and learning achievement, the average score was 87 with a percentage of 87% being in very good category. Based on the results above, it can be seen that the increase in thematic learning activities from cycle I to cycle II was 21.44% and the increase in thematic learning achievement from cycle I to cycle II was 24.58%. Based on the analysis of the data, it can be concluded that the use of electronic student worksheets containing multimedia can increase student activity and learning achievement.